Conducting a culturally informed neuropsychological evaluation - Fujii, Daryl, 1961- (American Psychological Association, 2017)
"While experienced neuropsychologists may be well-versed in the standard process of conducting a neuropsychological evaluation, they may still have difficulty determining a client's current functioning, given his or her unique cultural context. This is especially true when the client and the clinician do not share the same ethnic background and language fluency. In such cases, the clinician risks administering a biased assessment with invalid tests, misinterpreted data, and inappropriate -- if not harmful -- treatment recommendations. Daryl Fujii helps neuropsychologists enhance their cultural competence by providing readers with a broad framework for cultivating an ethnorelative -- instead of an ethnocentric -- view of clients. He begins by reviewing relevant research and professional guidelines that explain how cultural factors can impact a neuropsychological evaluation. Then he outlines preliminary strategies for establishing rapport and improving communication with clients, estimating their premorbid functioning, gathering pertinent data, selecting and translating appropriate tests, and working with interpreters. The closing chapters present a detailed case example that demonstrates a pre-assessment interview, test interpretation, report writing, treatment recommendations, and a final feedback session with the client"--Publicity materials. (PsycINFO Database Record (c) 2016 APA, all rights reserved).